Efektivitas Media Puzzle GESIT terhadap Peningkatan Pengetahuan, Sikap, dan Perilaku Remaja Awal: The Effectiveness of the GESIT Puzzle Media on Improving Knowledge, Attitudes, and Behaviors of Early Adolescents - Syawalna Putri Azizah; Megah Stefani (Amerta Nutrition, 2025)
Background: The prevalence of obesity among adolescents in Indonesia continues to rise and has become a serious health concern due to its negative effects on both physical and psychosocial well-being. One contributing factor is the lack of early education on the principles of balanced nutrition. Objectives: This study aims to evaluate the effectiveness of the educational media Balanced Nutrition Puzzle for Obesity Prevention Education (GESIT) in improving early adolescents' knowledge, attitudes, and behaviors related to obesity prevention. Methods: This study employed a pre-experimental, one-group pre-test-post-test design. A total of 63 fourth- and fifth-grade students at Madrasah Ibtidaiyah Roudlatul Jannah were selected using purposive sampling. The educational medium used was the GESIT puzzle, which was validated by two experts: a content (material) expert and a media expert. The intervention consisted of two educational sessions using the GESIT puzzle, followed by students' independent practice for 5 days. The feasibility test results showed scores of 87.5% from the content expert and 85% from the media expert. Results: The study found increases in the proportions of participants in the high category for knowledge from 0% to 63.5%, attitudes from 55.6% to 81.0%, and behavior from 34.9% to 73.0% after the intervention. Improvements in knowledge, attitudes, and behavior were statistically significant (p-value<0.001). Conclusions: Thus, it can be concluded that the GESIT puzzle media is effective in improving early adolescents' knowledge, attitudes, and behavior.